Theoretical modeling of current measurement in nanoscale device considering Green's function formalism - Hassan, Asif S.; Mondol, Raktim Kumar; Jafar, Imran Bin; Shahin, Md Zahidul Islam (© 2015 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 2nd International Conference on Advances in Computer Engineering and Applications, ICACEA 2015; IMS Engineering CollegeGhaziabad; India; 19 March 2015 through 20 March 2015 [© 2015 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://10.1109/ICACEA.2015.7164850